Impacto da pandemia da Covid-19 nos atendimentos odontológicos para usuários idosos em serviços de pronto atendimento da cidade de Manaus-AM - Costa, Adriane Araújo (Brasil, 2023)
This study aimed to compare the number of dental appointments in emergency services for elderly users in the city of Manaus-AM, before and during the worst moment of the pandemic. This is a retrospective cross-sectional study based on secondary data from the dental records of six units that offer emergency care services in the city, at the two stipulated times: december 2019, january, february 2020 and january, february and march 2021. Descriptive data analysis was perfomed based on central tendency measures for quantitative variables and frequencies for categorical variables. Data normality was tested using Kolmogorov-Smirnov statistics, aiding the bivariate analysis. Associations between categorical variables were tested using Pearson’s chi-square statistic with a significance level of 95%. Differences between mean ages and categorical variables were tested using the Mann-whitney “U” or Kruskal-wallis “H” statistic, both with 95% confidence. 133 consultations (84.2%) occurred in pre-pandemic period and 25 (15.8%) during the pandemic. It was also observed that 55.7% of users were male, with a mean age of 67.34 (± 6.96) years. Male individuals were the ones who most sought the services with complaints of toothache, abscess and others, when compared to female individuals (p=0,03). In only four records (2.53%) there were notes about the systemic condition of the elderly, revealing a low completeness of this variable. In view of this, there is an imminent need for training of dentists in the services evaluated in terms of filling out these medical records, making the information contained therein valid and indisputable management tools.